Improved Theory of the Effective Dipole Moments and Absolute Line Strengths of the XY2 Asymmetric Top Molecules in the X2B1 Doublet Electronic States; International Journal of Molecular Sciences; Vol. 24, iss. 16 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Kakaulin A. N. Aleksey Nikolaevich; Sydow Ch. Christian; Bauerecker (Bauerekker) Z. (S.) H. Zigurd (Sigurd) Hermann (2023, 2023)
Title screen